Nichtvirale sexuell übertragene Infektionen: Epidemiologie, Klinik, Labordiagnostik und Therapie : Teil 1: Gonokokken - Nenoff, Pietro; Helmbold, Peter (Der Hautarzt, 2017)
Approximately 1 million people are infected per day worldwide by one or more sexually transmitted infections (STI) as estimated by the World Health Organization (WHO). Gonorrhoea represents an almost exclusively sexually transmitted infection, which predominantly affects mucous membranes of the genitourinary tract. Extragenital localization of infections is also possible, e. g. in the anorectal region. Currently, only syphilis and human immunodeficiency virus (HIV) are notifiable diseases according to the Infection Protection Act in Germany. In Saxony, an extended registration ordinance according to the German Infection Protection Act is in force, which means that besides syphilis the laboratory detection of Neisseria gonorrhoeae, Chlamydia trachomatis and genital mycoplasms are also notifiable infections. In particular, beginning in 2009 in Saxony a spectacular increase of registered infections due to N. gonorrhoeae was observed and in 2015 altogether 824 infections due to N. gonorrhoeae were reported. Alarming is the increase in resistance of N. gonorrhoeae against penicillin, doxycycline, ciprofloxacin and recently also against azithromycin and third generation cephalosporins. The so-called superbug of N. gonorrhoeae, which originated in Japan with multidrug resistance against most of the currently available oral antibiotics, has now arrived in Europe. Intramuscular or intravenous injection of ceftriaxone plus oral azithromycin, each given as single dose is the standard therapy for gonorrhoea.
Online publiziert: 15. Dezember 2016
Gesehen am 03.05.2018